Ethnobotanical survey of medicinal plants in Sissala East municipality of the upper West region, Ghana - George Dery; Selasi Dzitse; Damian Tom-Dery (Phytomedicine Plus, 2023)
The questionnaires contained a checklist of questions that included plant names, diseases treated, plant parts used, mode of preparation/administration, and sources of medicinal plants. A total of 94 medical plant species were documented and used to treat 79 health afflictions. The most cited plant family was Fabaceae (23.4%). Annonaceae (1.0%) and Loganiaceae (1.0%) were among the least cited plant families. Woody tree species (50%) and herbs (30.9%) were the major sources of herbal medicines and plant parts such as leaves (44.6%) and stem bark (22.79%) were the most used parts in the preparations of herbal medicines. The commonest method used to prepare most medicines was decoction (67%) while Chewing (1%), and extraction of juice (1%) were the least methods. Oral (71%) and topical (24%) methods were the most used modes of administration with inhaling (1%) being the least. Parasitic infections recorded the highest use reports (23%) and the highest taxa of (19%). There was strong informant agreement on the use of medicinal plants for treating digestive system disorders (ICF: 0.59) and microbial disorders (ICF: 0.50). These results showed a good diversity of medicinal plants in the Municipality.